The status of education for sustainability in initial teacher education programmes: a Canadian case study. Issue 4 (26th August 2014) - Falkenberg, Thomas; Babiuk, Gary
Abstract : Purpose: – The purpose of this paper is to establish the status of education for sustainability in the teacher education programmes in the province of Manitoba in Canada and to identify challenges and obstacles for mainstreaming education for sustainability in those programmes. Design/methodology/approach: – Using a multi-unit case study design, online programme information and data from interviews with faculty administrators and a convenience sample of faculty members from all five faculties of education in Manitoba were collected and analysed. Findings: – There is no systematic and focused preparation of teachers for education for sustainability in any of the Manitoba teacher education programmes. Three challenges for mainstreaming of education for sustainability are identified: lack of leadership, an unfavourable view of the role of education for sustainability and the silo-ing within faculties of education. Research limitations/implications: – The research is limited by its focus on the programme-based implementation of education for sustainability in faculties of education, which did not include any course-based implementation by individual instructors. Practical implications: – To address the challenges and obstacles for mainstreaming, the authors argue for joint leadership across the relevant institutional levels (government, university and faculty), and for establishing education for sustainability as a framework for responding to the purpose question of school education. Originality/value: – The study provides empirical evidence for some of the major challenges for mainstreaming education for sustainability in faculties in education and, by generalisation, all university faculties.